Effects of Pollution and Transportation on Public Health in Jakarta - Agung Zulfikri (Westscience Press, 2023)
This study aims to investigate the impact of pollution and transportation on public health in Jakarta, Indonesia. Data was collected from a cross-sectional survey of 500 residents in Jakarta, including measurements of exposure to air and noise pollution, transportation behavior, and health status. The results showed that the use of private transportation was associated with higher exposure to air and noise pollution, while the use of public transportation was associated with lower exposure. Exposure to pollution has also been linked to poor health outcomes such as respiratory and cardiovascular diseases and mental health problems. The findings highlight the need for measures to reduce pollution exposure and promote the use of public transport and active modes of transport to improve public health in Jakarta. More research is needed to investigate the long-term impacts of pollution and transport on public health and to identify effective interventions to reduce those impacts.